Extraction of Value-Added Products from Empty Fruit Bunch by Using Supercritical CO2 and Water as Co – Solvent - Yim, See Cheng (Universiti Teknologi PETRONAS, 2016)
Recently, about 34.44 million tonne of oil palm biomass was produced in Malaysia with empty fruit bunch (EFB) as major compounds. This is due to the high market demand for palm oil in the world. The value-added products which are phenolic compounds and fatty acids from EFB were extracted using supercritical carbon dioxide (Sc-CO2) and water as co-solvent. This is because Sc-CO2 extraction is a feasible and environmental friendly technology. In this study, Sc-CO2 extraction of EFB was carried out under several experimental parameters such as temperature, pressure and particles size that varies in the range of 40 - 90°C, 20 - 40 MPa and 0.15 mm - 2.20 mm, respectively.